Anti-citrullinated protein antibody positivity correlates with cartilage damage and proteoglycan levels in patients with rheumatoid arthritis in the hand joints - Renner, Nina; Krönke, Gerhard; Rech, Jürgen; Uder, Michael; Janka, Rolf Matthias; Lauer, Lars; Paul, Dominik; Herz, Barbara; Schlechtweg, Philipp; Hennig, Friedrich; Schett, Georg; Welsch, Götz (Arthritis and Rheumatology, 2014)
Objective: To investigate the factors associated with cartilage proteoglycan content in patients with rheumatoid arthritis (RA) Methods: 32 RA patients received high-field 3 Tesla Gadolinium-Enhanced MRI of Cartilage (dGEMRIC) for determining cartilage proteoglycan content. Measurements were performed in three individual cartilage regions (medial, central, lateral) of the metacarpophalangeal joints 2 and 3. dGEMRIC values were then related to disease duration, disease activity, anti-citrullinated protein antibody (ACPA) status, rheumatoid factor status and C-reactive protein level. Results: dGEMRIC values were not significantly different between the MCP2 and MCP3 joint. Inter-class correlations were high (>0.92) for all three (medial, central and lateral) cartilage compartments. dGEMRIC values were significantly lower in RA patients with longer disease duration (>=3 years) and those with ACPA positivity than those with a short disease duration (<3 years)(p=0.034) or negative ACPA (p=0.0002), respectively. In contrast, no association between cartilage proteoglycan content and disease activity, C-reactive protein level and rheumatoid factor status was found. Conclusion: Decreased cartilage proteoglycan content in RA patients is associated with disease duration and ACPA positivity but not with the actual disease activity, CRP level or rheumatoid factor status. These data suggest that the cumulative burden of inflammation as well as ACPA are the determinants for cartilage damage in RA.
EVALuna2:12983